Population Genetic Structure of the Endangered Brasenia schreberi in South Korea Based on Nuclear Ribosomal Spacer and Chloroplast DNA Sequences - Kim, C.K., Ajou University, Suwon, Republic of Korea; Jung, J.D., Ajou University, Suwon, Republic of Korea; Na, H.R., Ajou University, Suwon, Republic of Korea; Kim, S.W., Biological Resource Center, KRIBB, Daejeon, Republic of Korea; Li, Wei, Chinese Academy of Sciences, Wuhan, Hubei, People's Republic of China; Kadono, Yasuro, Kobe University, Kobe, Japan; Shin, H.C., Soonchunhyang University, Asan, Republic of Korea; Choi, H.K., Ajou University, Suwon, Republic of Korea (Journal of Plant Biology, 2012)
Genetic variation of nuclear ribosomal ITS (nrITS) and chloroplast DNA (cpDNA) regions was investigated in Brasenia schreberi (Cabombaceae) to assess the population structure and to infer the evolutionary relationship among 12 populations distributed in South Korea. The combined sequence of the two regions was aligned to 2,069 bp, of which 28 sites were variable. In total, 20 genotypes were identified from 240 individuals of B. schreberi. Genotype diversity (Gd) and nucleotide diversity (Pi) on Jeju Island (Gd = 0.2511, Pi = 0.00012) were higher than those of the mainland of South Korea (Gd = 0.1358, Pi = 0.00005). The relatively low level of genetic variation of the mainland populations is associated with its higher genetic differentiation (G∧ST = 0.095 on mainland and 0.039 on Jeju Island) and human activities. Minimum spanning network analysis demonstrated that the investigated populations of B. schreberi were subdivided into two geographical groups: the mainland of South Korea and Jeju Island. In addition, analysis of molecular variation showed that a large proportion (73.55%) of genetic differentiation existed between the two regions. These results strongly suggest the presence of significant barriers to gene flow between regions. Thus, the management unit for B. schreberi should be carefully designed to avoid the potential risk that can results from the admixture of individuals from the mainland and Jeju Island regions.